School Management and Inclusive Education: a needed and emergent partnership at the school - Maria Antonia Ramos de Azevedo; Gracilliani Rosa da Cunha (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
The objective of this research was to highlight the relationship between the management school team and inclusive education practices. A literature review brought up warnings regarding the complexity of such process. It has to account for public policies related to inclusive education, the curriculum structure and the Political Pedagogic Project (PPP), the role of the teacher practices and the contribution of the school management team. The present analysis points toward the need to reassess the public policies and the school management team practices. It is concluded that there is a need to change the strategies used to deal with problems related to inclusion in the school by collecting insights and building solutions from community, as well as public regulations that support such initiatives. To reach a "school for all" it has to be "done by all", that is, school, community and family.